2018
DOI: 10.1155/2018/3473910
|View full text |Cite
|
Sign up to set email alerts
|

Enjoy the Benefit of Network Coding: Combat Pollution Attacks in 5G Multihop Networks

Abstract: In the upcoming 5G era, many new types of networks will greatly expand the connectivity of the world such as vehicular ad hoc networks (VANETs), Internet of Things (IoT), and device-to-device communications (D2D). Network coding is a promising technology that can significantly improve the throughput and robustness of these emerging 5G multihop networks. However, network coding is generally very fragile to malicious attacks such as message content corruption and node compromise attacks. To take advantage of net… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 30 publications
0
3
0
1
Order By: Relevance
“…Chen et al proposed a method of applying error detection and error correction techniques to encoded packets. This paper showed that the throughput can be improved by allowing the intermediate nodes to correct the packet [12]. Mamidwar et al analyzed studies to prevent the rapid spread of pollution attacks from network coding throughout the network.…”
Section: Related Workmentioning
confidence: 99%
“…Chen et al proposed a method of applying error detection and error correction techniques to encoded packets. This paper showed that the throughput can be improved by allowing the intermediate nodes to correct the packet [12]. Mamidwar et al analyzed studies to prevent the rapid spread of pollution attacks from network coding throughout the network.…”
Section: Related Workmentioning
confidence: 99%
“…In fact, in cryptography, homomorphic signature scheme is another technique to protect network coding against pollution attack [3]- [5], [11]. Contrast to homomorphic MAC scheme, it is a kind of public key authentication method.…”
Section: A Related Workmentioning
confidence: 99%
“…It is a new concept. Study on the performance of network coding shows that it can utilize the available limited bandwidth of the network to achieve improved throughput in multicast communication [16] [31] [32]. Network coding is applied on on-demand broadcasting network [14] [23] [28].…”
Section: Introductionmentioning
confidence: 99%